2022
DOI: 10.53850/joltida.980931
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Views Regarding Instruction during the Pandemic Process

Abstract: The aim of this study was to determine the views of secondary and high school students regarding the distance education activities carried out during the coronavirus disease 2019 (COVID-19) pandemic, the blended learning activities conducted afterwards, and the post-pandemic back-to-school process. The study consisted of 982 students and was conducted utilizing the descriptive survey method, one of the quantitative research methods. Data were collected using the "Scale of Evaluating Instruction in Pandemic Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…Similarly, Doğan (2020), Gören et al (2020) and Sayan (2020) also stated that distance education evaluation scores make a significant difference in terms of gender. However, Bircan et al (2018), Düz and Sulak (2020), Hasançebi et al (2022), Karadağ and Yücel (2020) and Yılmaz (2020) no significant difference observed between the groups in terms of gender. According to these findings, gender demonstrates an influence on students' performance.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, Doğan (2020), Gören et al (2020) and Sayan (2020) also stated that distance education evaluation scores make a significant difference in terms of gender. However, Bircan et al (2018), Düz and Sulak (2020), Hasançebi et al (2022), Karadağ and Yücel (2020) and Yılmaz (2020) no significant difference observed between the groups in terms of gender. According to these findings, gender demonstrates an influence on students' performance.…”
Section: Discussionmentioning
confidence: 95%